2001
DOI: 10.1139/w00-117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cymbopogon nardus (L.) W. Watson essential oil on the growth and morphogenesis of Aspergillus niger

Abstract: The growth inhibitory effect of Cymbopogon nardus (L.) W. Watson var. nurdus essential oil on Aspergillus niger (Van Tieghem) mycelium was determined on agar medium. The mycelium growth was completely inhibited at 800 mg/L. This concentration was found to be lethal under the test conditions. Essential oil at 400 mg/L caused growth inhibition of 80% after 4 days of incubation, and a delay in conidiation of 4 days compared with the control. Microscopic observations were carried out to determine the ultrastructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
0
9

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(96 citation statements)
references
References 21 publications
13
74
0
9
Order By: Relevance
“…It has been shown that EOs are able to cause morphophysiological changes in Aspergillus species including loss of sporulation and pigmentation and aberrant development of both hyphae and reproductive structures (De Billerbeck et al 2001). Morpho-physiological changes were documented in all tested isolates in our study, such as lack of sporulation, depigmentation of conidiogenous apparatus and conidia, terminal and intercalar swellings and apical buddings.…”
Section: Morpho-physiological Changessupporting
confidence: 51%
See 1 more Smart Citation
“…It has been shown that EOs are able to cause morphophysiological changes in Aspergillus species including loss of sporulation and pigmentation and aberrant development of both hyphae and reproductive structures (De Billerbeck et al 2001). Morpho-physiological changes were documented in all tested isolates in our study, such as lack of sporulation, depigmentation of conidiogenous apparatus and conidia, terminal and intercalar swellings and apical buddings.…”
Section: Morpho-physiological Changessupporting
confidence: 51%
“…It is reported that application of EOs may result in retraction of cytoplasm and interaction of EO components with fungal cell wall (Carmo et al 2008). There also may be interference in enzymatic reactions of cell wall synthesis, which affects fungal growth and morphogenesis (De Billerbeck et al 2001, Souza et al 2010. The fact that structural changes were observed in all fungal isolates tested in this study indicates that O. vulgare EO can affect the morphological development of different Aspergillus species and probably other fungi as well.…”
Section: Morpho-physiological Changesmentioning
confidence: 71%
“…The inhibitory effect of the oils was proportional to their concentration. Studying effects of C. nardus, known as Ceylon citronella oil, on fungal growth and morphogenesis of Aspergillus niger, de Bilerbeck et al (2001) found that essential oil had been lethal for A. niger, causing plasma membrane disruption and mitochondrial structure disorganizations. Earlier reports indicate some contradictions in activity of C. nardus essential oil.…”
Section: Resultsmentioning
confidence: 99%
“…Irreversible morphological changes in the cell wall and plasma membrane of A. flavus caused by Ageratum conyzoides extract have been reported [16]. de billerbeck et al [17] reported a decrease in the cell wall thickness of A. niger caused by the essential oil of Cymbopogon nardus. These suggest that the cell wall could be one of the target sites of action of plant extracts.…”
Section: Discussionmentioning
confidence: 94%